Effect of polysaccharide extracted from Klebsiella pneumoniae in the immune system of albino mice against infection with secondary hydatid disease I.Growth and development of hydatid cysts and blood picture - Ibrahim Ali (College of Education for Pure Sciences, 2012)
Abstract The Present study investigated the effect of the polysaccharide extracted from the bacteria Klebsiella pneumoniae on immune response of white mice expermentaly infected with secondary hydatid disease caused by Echinococcus granulosus. Criteria taken into consideration included the changes in numbers, weights and diameters of the hydatid cysts and the percentage of their reduction, in addition, changes in weights of liver and spleen and their organ index. The changes in total and differential count of WBCs in peripheral blood of mice treated with polysaccharide in comparision with the positive control (mice infected with secondary hydatid disease and not treated with polysaccharide) and negative control (mice neither treated with polysaccharide, nor infected with hydatid disease), three month post infection, was studied. The results revealed a decrease in numbers, weights and diameters of hydatid cysts in mice treated with the polysaccharide in comparison with positive and negative control, supported by the reduction of cyst numbers in treated mice. A decrease in weights and organ index of the liver in treated mice compared with positive control, increase in the weights and organ index of spleen in treated mice compared with positive and negative control, An increase in total count of WBCs, Regarding the differential count of WBCs, an increase in the percentage of lymphocytes and decrease in the percentage of monocytes, neutrophils and eosinophils in treated mice in comparision with positive and negative control, was observed, Basophils were neglected because of their rarity. It can be concluded that the polysaccharide extracted from K.pneumoniae can be used as an active and non toxic immunomodulator against infection with secondary hydatid disease in white mice.